Neuroprotection by Therapeutic Hypothermia - Ying-Jian Sun (Frontiers in Neuroscience, 2019)
Hypothermia therapy is an old and important method of neuroprotection. Until now, many neurological diseases such as stroke, traumatic brain injury, intracranial pressure elevation, subarachnoid hemorrhage, spinal cord injury, hepatic encephalopathy, and neonatal peripartum encephalopathy have proven to be suppressed by therapeutic hypothermia. Beneficial effects of therapeutic hypothermia have also been discovered, and progress has been made toward improving the benefits of therapeutic hypothermia further through combination with other neuroprotective treatments and by probing the mechanism of hypothermia neuroprotection. In this review, we compare different hypothermia induction methods and provide a summarized account of the synergistic effect of hypothermia therapy with other neuroprotective treatments, along with an overview of hypothermia neuroprotection mechanisms and cold/hypothermia-induced proteins.